2018
DOI: 10.1016/j.jbi.2018.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and challenges of behavior change support systems for enhancing habit formation: A qualitative study

Abstract: For sustainable weight management, holistic e-health interventions are required, and the PSD model offers a practical approach for designing and developing them. Recognizing the stages of habit formation provides additional valuable guidance for designing systems that help shape an individual's habits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 75 publications
2
16
0
Order By: Relevance
“…Participants in this study also considered that intervention usage and engagement rates would likely be higher soon after surgery, but reduce over time once they better adjusted to post-surgical life. These thoughts echo similar ndings within the literature that support engagement decline, however these were previously related to a novelty phenomenon associated with digitally-supported care, (58,59) rather than a result of reduced patient support-requirements. This draws attention to the importance of nding optimal 'engagement balance' with any digital health technologies implemented for patients.…”
Section: Study Participants Describedsupporting
confidence: 85%
“…Participants in this study also considered that intervention usage and engagement rates would likely be higher soon after surgery, but reduce over time once they better adjusted to post-surgical life. These thoughts echo similar ndings within the literature that support engagement decline, however these were previously related to a novelty phenomenon associated with digitally-supported care, (58,59) rather than a result of reduced patient support-requirements. This draws attention to the importance of nding optimal 'engagement balance' with any digital health technologies implemented for patients.…”
Section: Study Participants Describedsupporting
confidence: 85%
“…Moreover, the application has been systematically developed with a set of persuasive software features being carefully selected, designed and programmed into the application for improving patients' behaviour. User experience studies of these persuasive features have been reported earlier [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…The 52-week ICT intervention was designed and developed by using the Persuasive Systems Design methodology [20] for the PrevMetSyn study as a Health Behaviour Change Support System (HBCSS) [21], technically as a web-based information system based on a cognitive behavioural approach [22,23]. The main characteristics are weekly health-related contents, information on healthy lifestyle and self-monitoring related software functionalities.…”
Section: Interventionsmentioning
confidence: 99%
“…It makes sense that changes in attitude would be important when the desired outcomes of an online system involve the desire for changes in behavior. Other key components involved with BCSS that also overlap with the study findings are the idea that systems should be user friendly and include persuasion to illicit meaningful behavior change [50][51][52][53][54]. When considering online alternatives to suspension it would be crucial to use the tenants involved with the BCSS perspective to help evaluate current options to identify programs that would have impact and appropriate usability.…”
Section: Discussionmentioning
confidence: 99%